Fixed-Time Event-Triggered Stabilization of High-Order Nonlinear Systems With Asymmetric Output Constraints - Zhaoyang Han; Jiao-Jiao Li; Xian-Long Yin; Yongpeng Ma; Shiji Ren (IEEE Access, 2024)
This paper presents the issue of a new fixed-time event-triggered control strategy for a class of high-order uncertain nonlinear systems with asymmetric output constraints. The key technique of this paper is to employ a new event-triggered strategy by combining the Barrier Lyapunov Function (BLF) and the power integral function of the embedded symbolic function. The approach employs a proof by contradiction to rigorously establish that the Zeno phenomenon is precluded from occurring. By circumventing the problem of non-differentiability at some discrete points, it avoids the necessity for the derivative of the event-triggered error. Moreover, the designed controller ensures the fixed-time stability of the system and also prevents the output from exceeding the preset constraints. Finally, based on numerical simulations, the effectiveness and superiority of the proposed control strategy are demonstrated through practical simulation examples and comparative experiments.